Pengaruh PENGARUH CITRA MEREK DAN ULASAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN COSMETIC PINKFLASH PADA PLATFORM SHOPEE DENGAN MENGGUNAKAN MEDIASI CONSUMER TRUST - Rodiyah, Muhimmatur; Fadiyah, Farah; Muzdalifah, Laily (Airlangga Journal of Innovation Management, 2025)
This study aims to investigate the influence of brand image and product reviews on purchase decisions of PinkFlash cosmetics through the Shopee platform, with consumer trust serving as a mediating variable. Using a quantitative method with Partial Least Squares-Structural Equation Modeling (PLS-SEM), data were collected from 160 respondents who had purchased PinkFlash products. The findings show that brand image has a strong and significant effect on consumer trust and purchase decisions, while product reviews significantly influence trust but do not directly affect purchase behavior. However, trust effectively mediates the relationship between brand image and purchase decisions, as well as between product reviews and purchase decisions, highlighting its central role in reducing uncertainty and reinforcing consumer confidence in online shopping. The results also indicate that despite the brand’s temporary crisis related to the discovery of hazardous substances, positive reviews and a favorable brand image remain critical in rebuilding consumer trust. Theoretically, this research contributes to consumer behavior literature by emphasizing trust as both a mediating and direct determinant in e-commerce cosmetics. Practically, the study offers managerial implications for online cosmetic brands to strengthen brand image and manage reviews strategically in order to foster trust and drive purchase decisions, particularly among Generation Z consumers.